Hacking exposed wireless wireless security secrets & solutions - Wright, Joshua; Cache, Johnny (McGraw-Hill Education, 2015)
Overview: Exploit and defend against the latest wireless network attacks. Learn to exploit weaknesses in wireless network environments using the innovative techniques in this thoroughly updated guide. Inside, you'll find concise technical overviews, the latest attack methods, and ready-to-deploy countermeasures. Find out how to leverage wireless eavesdropping, break encryption systems, deliver remote exploits, and manipulate 802.11 clients, and learn how attackers impersonate cellular networks. Hacking Exposed Wireless, Third Edition features expert coverage of ever-expanding threats that affect leading-edge technologies, including Bluetooth Low Energy, Software Defined Radio (SDR), ZigBee, and Z-Wave. Assemble a wireless attack toolkit and master the hacker's weapons. -- Effectively scan and enumerate WiFi networks and client devices. -- Leverage advanced wireless attack tools, including Wifite, Scapy, Pyrit, Metasploit, KillerBee, and the Aircrack-ng suite. -- Develop and launch client-side attacks using Ettercap and the WiFi Pineapple. -- Hack cellular networks with Airprobe, Kraken, Pytacle, and YateBTS. -- Exploit holes in WPA and WPA2 personal and enterprise security schemes. -- Leverage rogue hotspots to deliver remote access software through fraudulent software updates. -- Eavesdrop on Bluetooth Classic and Bluetooth Low Energy traffic. -- Capture and evaluate proprietary wireless technology with Software Defined Radio tools. -- Explore vulnerabilities in ZigBee and Z-Wave-connected smart homes and offices. -- Attack remote wireless networks using compromised Windows systems and built-in tools